2010
DOI: 10.31899/pgy1.1022
|View full text |Cite
|
Sign up to set email alerts
|

White paper: Enhancing adolescent financial capabilities through financial education in Bangladesh

Abstract: Department for International Development (DfID) aims to improve the lives of adolescents, women and the poor people of the developing nations including Bangladesh. Financial literacy programs are one of the avenues to bring such changes. We are grateful to the DfID Bangladesh for sponsoring the pilot study and endeavor to write a white paper to set the discourse and futures of the financial literacy programs for Bangladesh. Barbara Payne, Senior Education Advisor, and Fazle Rabbani, Advisor, DfID, played key r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…A study on cash transfers to adolescent girls in Malawi showed that girls who received the cash transfer had a decline in early marriage, teenage pregnancy and self-reported sexual activity (Baird, Chirwa, Mcintosh & Ozler, 2010). A study with adolescent girls in Bangladesh showed that adding a financial education component to life-skills resulted in significantly greater positive impact in changing sexual behaviors (Amin et al, 2010).…”
Section: Background and Theorymentioning
confidence: 98%
“…A study on cash transfers to adolescent girls in Malawi showed that girls who received the cash transfer had a decline in early marriage, teenage pregnancy and self-reported sexual activity (Baird, Chirwa, Mcintosh & Ozler, 2010). A study with adolescent girls in Bangladesh showed that adding a financial education component to life-skills resulted in significantly greater positive impact in changing sexual behaviors (Amin et al, 2010).…”
Section: Background and Theorymentioning
confidence: 98%
“…The baseline report includes frequencies of selected indicators and cross-tabulations by age using STATA. For categorical variables, significance tests comparing younger girls (ages [11][12] and older girls (ages [13][14] were estimated using Pearson's Chi Square. For continuous variables, linear regression models were estimated using options for obtaining robust standard errors in the Kibera dataset and adjusting for clustering by village in the Wajir dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from two recent studies indicates that savings and financial education are effective methods of economic strengthening for adolescent girls -especially considering the young age of the girls and the approach of building direct assets for the girls themselves, as opposed to strengthening the household economic status and looking for a trickle-down effect to the girls. 13,14 Research Methodology…”
Section: Wealth Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…Social isolation, economic vulnerability, and lack of access to health care and education prevent healthy transitions from childhood to adulthood, especially for adolescent girls in developing countries. [1][2][3][4][5] In Zambia, poor girls are often at higher risk of gender-based violence and HIV than their male age-mates. 6 Many girls drop out of school, are unable to find employment, lack the ability to make independent decisions, and are not being reached by existing programs for young people.…”
Section: Adolescent Girls Empowerment Program (Agep): Healthmentioning
confidence: 99%